APPLICATION OF THE PRINCIPLE OF TEMPUS REGIT ACTUM IN THE ESTABLISHMENT OF A STATE-OWNED ENTERPRISE HOLDING COMPANY ACCORDING TO THE LEGAL CONCEPT OF COMPANIES IN INDONESIA - Ramlan (Pena Cendekia Insani, 2026)
The establishment of a BUMN holding company aims to create synergy between companies, increasing operational and cost efficiency, increasing business scale, strengthening financial position (solvency and liquidity), as well as facilitating coordination, accelerating growth (acquisitions), and increasing contribution to state revenue. The type of research used is normative legal research with a legal synchronization level approach. The nature of the research is descriptive, using secondary data, especially from primary legal materials such as UUBUMN, UUUPT, the next type of research was analyzed qualitatively. Article 10 paragraph (2) of the UUBUMN No. 16/2025 states that the establishment and management of holding companies are carried out in accordance with the provisions governing limited liability companies. However, because specific regulations for the establishment of holding companies have not been regulated, the government applies the principle of tempus regit actum, so that the establishment of holding companies uses the rules for establishing company acquisitions.